Anthropometric characteristics in Bangladeshi elite female gymnasts - Arafat, Y.; Rickta, J. F.; Mukta, F. T. J.; Islam, R.; Iqbal, A. (American Journal of Sports Science, 2023)
Background: Gymnastics is a world popular oldest game which star in the ancient Olympic Games. Human body is the most research topic nowadays. An anthropometric profile is a scientific and systematic study of human body size, shape, and propositions. Objective: The Purpose of the study is to help to know about Bangladeshi elite female gymnast anthropometric characteristic and compare with the Olympic level gymnast. The research knowledge also help to develop training methods that enhance their performance. Method: A total of twenty female gymnastic players as the subject for this present study, all gymnast participates both national and international level competition. All the subjects lived in Bangladesh Krira Shikkha Protishtan (BKSP), Dhaka and their training age were between two to six years. The anthropometric profile was assessed by measuring height, weight, arm length, leg length, shoulder width, hip circumference, and sitting height. The collecting data were analyzed using the standard statistical measure (Such as mean value, Standard Deviation, t value and p value also). Result: There is a considerable anthropometric difference between Bangladeshi and Olympic-level gymnasts and Bangladeshi gymnast because of they have behind the performance than the international level gymnast all over the world. Conclusion: Bangladeshi female elite gymnast have low anthropometric level than world level female gymnast.